Proceedings Frontiers in Education 1995 25th Annual Conference. Engineering Education for the 21st Century
DOI: 10.1109/fie.1995.483098
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the recruitment and retention of first-year students with improved career selection opportunities

Abstract: The paper describes an on-goingproject to improve thepersistence of jirst-year engineering technology majors. This project involves a pilot course that uses an experiential leaming approach to provide students with an improved understanding of engineering and technology. The teamtaught course also helps to develop the students' academic support system, including interaction with upper-class technology students. Initial evaluations indicate that the students found the attitude of the faculty, the active-leaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…7,11,14,15,18 Two studies were found that used written student evaluations and interviews to assess student opinions in more depth. 10,19 Retention studies have been used in a minority of cases, either alone 9 or in combination with a questionnaire. 8,12 The absence of a control group is pervasive, especially in studies that use a questionnaire.…”
Section: Assessment Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…7,11,14,15,18 Two studies were found that used written student evaluations and interviews to assess student opinions in more depth. 10,19 Retention studies have been used in a minority of cases, either alone 9 or in combination with a questionnaire. 8,12 The absence of a control group is pervasive, especially in studies that use a questionnaire.…”
Section: Assessment Methodologymentioning
confidence: 99%
“…7 Milano et al 8 describe how limiting the focus of an introductory course to a subset of engineering disciplines (usually mechanical, electrical, and either manufacturing or industrial) enabled the instructors to devote more time to each design effort. Dini et al, 9 McDonald, 10 and Rizkalla et al 11 used a similar approach, but also included some aspects of the success-based courses described earlier.…”
Section: Introductionmentioning
confidence: 94%
“…'professional engineering? or 'introduction to engineering', Course planners of introductory courses [18][19][20][21][22][23][24][25][26] wanted to see that the course "really is an introduction to engineering rather than just labelled that" [13]. Such courses were considered successful in developing an awareness of the engineering profession and, in particular, ways of thinking and attitudes necessary for the practitioner.…”
Section: A Newmentioning
confidence: 99%
“…Engineering and technology educators and administrators have written about retention issues extensively. [1][2][3][4][5][6][7][8][9] An important factor in retention is the first-year experience. 1 The body of work for increasing retention is differentiated by two types of instruction, one that offers lecture style, passive learning environments and the other that provides experiential learning with hands-on experience.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] An important factor in retention is the first-year experience. 1 The body of work for increasing retention is differentiated by two types of instruction, one that offers lecture style, passive learning environments and the other that provides experiential learning with hands-on experience. Each institution should reflect and examine it's own internal dynamics and reasons why students leave engineering technology programs as suggested by the study.…”
Section: Introductionmentioning
confidence: 99%